Understanding and valuing human connections to deep-sea methane seeps off Costa Rica - Pereira, Olívia Soares (2024)
Methane seeps are highly productive ecosystems that provide carbon sequestration services, host diverse communities including endemic species, and serve as habitats for commercial fisheries. Little is known about the economic value the public places on them. Discrete Choice Experiments (DCEs) are administered to a sample of Costa Rican taxpayers to evaluate their willingness to pay (WTP) in monetary terms using tradeoffs made in a survey context involving three of the main attributes of methane seep ecosystems to provide insights for future conservation and management efforts. Extensive effort is devoted to understanding how Costa Ricans view different aspects of the deep sea. We find that they associate it with strange animals, natural resources, the unknown, and being far from reach. Perhaps surprisingly, they underestimate how much they know about the deep sea. We find that WTP for methane seep protection is the highest for programs that protect seeps with endemic species, followed by seeps with high climate change mitigation potential and commercial fishing habitat. Higher-income groups and women are more likely to prefer options that increase the current level of protection. We discuss how science communication and community engagement contribute to care expressed toward the deep sea.